Perancangan UI/UX Aplikasi Pemesanan Guna Mengurangi Antrian Pelanggan di Coffe Shop AMPM Reborn dengan Metode Design Thinking - Maanary, Michellino Apriliandio; Putri, Erni Puspanantasari; Hermawati, Fajar Astuti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
AMPM Reborn, a coffee shop in Sidoarjo, faces recurring long queues during weekends, especially on Saturdays between 19:00–23:00. Customer waiting times reach 20–30 minutes, with queues extending up to 24 people, leading to reduced customer comfort and decreased service efficiency. This study aims to design a UI/UX website-based ordering system as a digital solution to streamline the ordering process and reduce physical queues. The research adopts the Design Thinking approach through the stages of empathize, define, ideate, prototype, and test, ensuring that the developed design aligns with user needs. A prototype was created using Figma and evaluated through usability testing to assess its effectiveness and ease of use. The results present an intuitive and efficient interface design that is expected to minimize waiting times and enhance overall customer satisfaction at AMPM Reborn.